CLASSICAL CULTURE, OPERA AND LITERATURE IN CONTEMPORARY YOUTH PRODUCTION: ANALYSIS OF THE WORK LA TRAVIATA, BY LEE GYEONG HYE, WITH ILLUSTRATIONS BY AURELIA FRONTY - Galvao Ribeiro Ferreira, Eliane Aparecida [UNESP]; Penavel Binato, Claudia Valeria [UNESP] (Unesp-faculdade Ciencias & Letras, 2016)
This paper presents an analysis of the work La Traviata, adapted by Lee Gyeong Hye (2012) and illustrated by Aurelia Fronty, from the homonym classic opera of Giuseppe Verdi. In order to achieve the objective, we aim to present a reflection based on the Aesthetics of Reception about what promotes pleasure in reading and which elements determine the role of the implicit reader. The hypothesis is constructed that Hye's strategy of rescuing a classical opera and adapting it in the form of illustrated narrative to the young reader, both gives him contact with an attractive, playful and critical text that will lead him to reflection, Broadens their knowledge, through the rescue of cultural memory.
Keywords: Opera; Aesthetics of reception; Classical Culture